Midline Congenital Upper Lip Sinus: A Rare Case - Chowdhary, Falak (Indian J Otolaryngol Head Neck Surg, 2018)
To present a rare case of a midline congenital upper lip sinus and its management. Background: A lip sinus is a rare condition, where a failure of the complete union during early stages of development leads to its formation. The prevalence of lower lip sinus is estimated to be about 0.00001% of the white population and that of upper lip sinus is even rarer. A congenital lip sinus maybe associated with syndromes such as; Von der Woude syndrome, or maybe present in isolation. A 25-year-old male presented to our clinic with intermittent swelling in the upper lip region. Clinical examination revealed a congenital midline lip sinus in the upper lip region, which had no intra-oral communication, and was managed by surgical excision. Till date, there has been a hand full of case reports of upper lip sinuses and fistulae, out of which only few are reported in India. We herein report a case of congenital upper lip sinus presenting as an intermittent swelling of the upper lip with its successful surgical management.